Saikosaponin A induces cellular senescence in triple-negative breast cancer by inhibiting the PI3K/Akt signalling pathway - Wu, Yingchao; Chen, Liushan; Pi, Dajin; Cui, Jiaqi; Liang, Yuqi; Wu, Peng; Ouyang, Mingzi; Zuo, Qian (Frontiers in Pharmacology, 2025)
BackgroundBreast cancer has now become the most prevalent cancer worldwide. Existing therapeutic agents are generally accompanied by significant side effects. Here, we highlight Saikosaponin A (SSA), a promising natural metabolite characterized by low toxicity, demonstrating significant efficacy against breast cancer through the induction of cellular senescence.MethodsThe antitumor property of SSA was determined via MTT colorimetric assay, 5-ethynyl-2′-deoxyuridine (EdU) incorporation assay, colony formation, and propidium iodide (PI) staining in vitro, as well as xenograft in vivo model. A network approach was used to predict potential targets of SSA reevant for a potential anti-tumor effect and verified through senescence-associated β-galactosidase (SA-β-gal), flow-cytometry analysis, RT-PCR, Western blotting, and immuno-histochemistry assay.ResultsSSA significantly suppressed proliferation and triggered cell cycle arrest of SUM159PT and MDA-MB-231 cells. Revealed by network analysis, cellular senescence, and phosphatidylinositol-3-kinase (PI3K)/Akt signaling pathway were implemented in the anti-tumor effects of SSA. SSA-stimulated senescence was associated with increased ROS production, distinct senescence-associated secretory phenotype (SASP), and restricted PI3K/Akt signaling, as well as p21 and p53 accumulation. Furthermore, SSA displayed inhibitory effects on tumor growth with minimal toxicity in animal studies, accompanied by activated biomarkers of cellular senescence and decreased expression of p-Akt and p-PI3K.ConclusionTaken together, based on the preliminary results of network analysis and further experimental validation, this study revealed that SSA significantly induced cell cycle arrest and senescence, and the inhibition of ROS-mediated PI3K/Akt pathway may be the potential mechanism in this process.